A Study of the Film Adaptations of Marek Hłasko's Prose by the Students of the Film School in Łódź - Justyna Bucknall-Hołyńska (Images)
A Study of the Film Adaptations of Marek Hłasko's Prose by the Students of the Film School in Łódź The works of Marek Hłasko have proved a reliable source of content and inspiration in Polish culture from the time of their writing to the current day, and this is demonstrated by the number of film adaptations of his literature. This article will look at Hłasko’s short stories that were written while the author lived in Poland and are collected in the book The First Step in the Clouds published in 1956. It will consider the subject matter and themes of the text, overview some examples of adaptations made by the students of the celebrated Łódź Film School, reflect as to how these have remained faithful or deviated from Hłasko’s original works, before concluding as to the reasons why the students may have been drawn to this particular source.